Reestructuración técnico administrativa en la empresa Emco Ltda. Con énfasis en la línea de producción de escaleras móviles (2017)
The technical and administrative reorganization of the company EMCO Ltda. is made in a company that manufactures and trades equipment for work at heights and transport of disabled people, in order to know the current state of the business and create some improvement actions throughout the manufacturing and administrative processes.